2018
DOI: 10.1530/erc-18-0028
|View full text |Cite
|
Sign up to set email alerts
|

Protein stabilization by RSUME accounts for PTTG pituitary tumor abundance and oncogenicity

Abstract: Increased levels of the proto-oncogene pituitary tumor-transforming gene 1 (PTTG) have been repeatedly reported in several human solid tumors, especially in endocrine-related tumors such as pituitary adenomas. Securin PTTG has a critical role in pituitary tumorigenesis. However, the cause of upregulation has not been found yet, despite analyses made at the gene, promoter and mRNA level that show that no mutations, epigenetic modifications or other mechanisms that deregulate its expression may explain its overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The PTTG family, which comprises PTTG1, PTTG2 and PTTG3P, is a newly identified gene class. Among the three homologous genes, PTTG1 has been the most extensively studied and has been identified to be closely associated with the onset and progression of multiple human cancer types, including pituitary tumor (22), malignant glioma (7), thyroid (23), breast (24), ovarian (25), bladder (8), prostate (9) and lung cancer (26–30). Honda et al (30) have demonstrated that PTTG1 is significantly upregulated in NSCLC and its overexpression serves a role in the genesis and progression of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The PTTG family, which comprises PTTG1, PTTG2 and PTTG3P, is a newly identified gene class. Among the three homologous genes, PTTG1 has been the most extensively studied and has been identified to be closely associated with the onset and progression of multiple human cancer types, including pituitary tumor (22), malignant glioma (7), thyroid (23), breast (24), ovarian (25), bladder (8), prostate (9) and lung cancer (26–30). Honda et al (30) have demonstrated that PTTG1 is significantly upregulated in NSCLC and its overexpression serves a role in the genesis and progression of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…RSUME is a novel and important player in pituitary tumor pathogenesis. RSUME also acts on the HPA axis at the pituitary stage, increasing pituitary tumor transforming gene (PTTG) protein stability ( 9 ) ( Figure 1B ). PTTG is the vertebrate securin ( 34 , 35 ) whose overexpression correlates with tumor invasiveness and recurrence.…”
Section: Biomolecular Modifications By Rsume In Neuroendocrine Cellsmentioning
confidence: 99%
“…This explains the effect of RSUME modulating PTTG high protein levels that account for PTTG tumor abundance and demonstrates an important role of RSUME in tumor cells of the pituitary. Regarding the molecular mechanism, we have described that PTTG protein levels decrease when the SUMOylation pathway is inhibited by the viral Gam1 protein ( 37 ), and the consequent reversal of this effect when an inactive mutant is used ( 9 ), suggesting that SUMO signaling is involved in the stabilization of PTTG. For many proteins, SUMOylation could protect them from degradation by the ubiquitin/proteasome system, in addition to increasing their stability, changing their subcellular localization or distribution, and/or modifying their molecular interactions.…”
Section: Biomolecular Modifications By Rsume In Neuroendocrine Cellsmentioning
confidence: 99%
“…Indeed, in recent years, mice xenografts have been widely used to characterize the responses to drugs currently prescribed for these pathologies as lanreotide (Ning et al 2009), thiazolidinediones (Mannelli et al 2010), bromocriptine and/or cabergoline (Lin et al 2017) or to alternative therapies such as metformin , histone deacetylase inhibitor SAHA (Lu et al 2017), Liquiritigenin (Wang et al 2014), Triptolide (Li et al 2017) or Bafilomycin A1 (McSheehy et al 2003), which have been shown to exhibit antitumoral roles in these pathologies. Likewise, PAs xenograft models have also been used to characterize the function of different pathways, genes and relevant mutations in several types of PAs, as Fgfr4 in intracranial xenograft mouse models (Ezzat et al 2006, Jalali et al 2016, inactivating mutations of Pit-1 (Roche et al 2012), overexpression of Lrig1 (Cheng et al 2016) or Meg3 (Chunharojrith et al 2015), persistent activation of the Ras/MAPK pathway (Booth et al 2014), antitumoral actions of miR-524-5p (Zhen et al 2017) and role of RSUME in PTTG protein stabilization (Fuertes et al 2018). Finally, PDX models have been sparsely implemented in the case of PAs.…”
Section: Models Of Pituitary Tumorsmentioning
confidence: 99%